Osteopetrosis: A rare cause of anemia - Review of literature - Saluja S; Bhandari S; Aggarwal S; Kapoor S (Wolters Kluwer Medknow Publications, 2009)
Normocytic anaemia is caused either by hypoproliferation of haemopoietic tissue or increased destruction of red cell. Osteopetrosis is a rare cause of anaemia. The leading clinical features are pallor, growth failure, hepatosplenomegaly.On hematological examination, anemia, thrombocytopenia, leucocytosis and myelophthisic anemia are commonly observed in this disease. We are highlighting osteopetrosis as a rare cause of anemia presenting to us for evaluation of anemia